A CO2 sink in a tropical coastal lagoon impacted by cultural eutrophication and upwelling. (5th December 2021) - Erbas, Thaís; Marques, Aguinaldo; Abril, Gwenaël
Abstract: Tropical coastal lagoons are recognized as very productive ecosystems. However, very little is known on the direction and magnitude of their CO2 exchange with the atmosphere. We report on air-water CO2 fluxes and carbon concentrations in a tropical shallow lagoon impacted by cultural eutrophication. During two contrasting field surveys, the first in Nov. 2019 during dry conditions and the second in Feb. 2020 during wet summer condition and intrusion of coastal upwelling waters inside the lagoon. At both seasons, spatial in situ monitoring of temperature, salinity and partial pressure of CO2 (pCO2 ) reveal the presence of undersaturated pCO2 values (between 60 and 300 ppmv), uptake of atmospheric CO2 (between 0.9 and 9.2 mmol m −2 h −1 ) inside the lagoon, at salinities between 10 and 32. Temporal monitoring data at the mouth of the lagoon throughout tidal cycles revealed the entrance of cold South Atlantic Central Waters (SACW) from the Cabo Frio's upwelling during flood tides in Feb. 2020 but not in Nov. 2019. The cold SACW with temperatures down to 16 °C were supersaturated in CO2 (pCO2 about 520 ppmv) and a CO2 source to the atmosphere (between 0.2 and 1.4 mmol m −2 h −1 ). During mixing of this SACW in the most marine compartment of the lagoon, the biological CO2 uptake and enhanced autotrophy overcame the effect of degassing SACW waters by heating. For both cruises, a consistent landward trend consisted in a decrease in pCO2 and dissolved inorganic carbon (DIC) mirrored by an increase of dissolved organic carbon (DOC) (between 4.6 and 19.8 mg L −1 ), particulate organic carbon (POC) (between 3.3 and 12.3 mg L −1 ), and chlorophyll a (Chl a ) (between 7.6 and 217 μg L −1 ). POC, DOC and Chl a and the POC:Chl a ratio suggest that, organic carbon in the lagoon is a mixture of phytoplankton biomass produced in the lagoon, domestic wastewater loaded from multiple point sources and pulsated inputs from small rivers. Our study in the Saquarema lagoon confirms recent works in other densely populated tropical coastal ecosystems, revealing that eutrophication enhances the autotrophy of shallow tropical lagoons, making them act as efficient factories for atmospheric CO2 absorption and organic carbon storage in sediments and export to the ocean. Highlights: The eutrophic Saquarema lagoon has a high phytoplanktonic biomass and behaves as a strong sink of atmospheric CO2 . The phytoplanktonic primary production was able to rapidly deplete in CO2 the supersaturated marine waters entering the lagoon during the upwelling period. Both particulate and dissolved organic carbon inside the lagoon was in majority of phytoplanktonic origin. The lagoon exported organic matter to the shelf water.